HUC-MSCs Exert a Neuroprotective Effect via Anti-apoptotic Mechanisms in a Neonatal HIE Rat Model. Issue 12 (December 2019) - Xu, Jianwei; Feng, Zhanhui; Wang, Xianyao; Xiong, Ying; Wang, Lan; Ye, Lan; Zhang, Huanxiang
In this study, we investigated how human umbilical cord mesenchymal stem cells exerted a neuroprotective effect via antiapoptotic mechanisms in a neonatal hypoxic-ischemic encephalopathy rat model. A total of 78 10-day old (P10) rats were used. After human umbilical cord mesenchymal stem cells were collected from human umbilical cords and amplified in culture, they were administered to rat subjects 1 h after induced hypoxic-ischemic encephalopathy treatment. The short-term (48 h) and long-term (28 day) outcomes were evaluated after human umbilical cord mesenchymal stem cells treatment using neurobehavioral function assessment. Triphenyltetrazolium chloride monohydrate staining was performed at 48 h. Beclin-2 and caspase-3 levels were evaluated with Western blot and real time polymerase chain reaction at 48 h. Human umbilical cord mesenchymal stem cells were collected and administrated to hypoxic-ischemic encephalopathy pups by intracerebroventricular injection. Hypoxic-ischemic encephalopathy typically induced significant delay in development and caused impairment in both cognitive and motor functions in rat subjects. Human umbilical cord mesenchymal stem cells were shown to ameliorate hypoxic-ischemic encephalopathy-induced damage and improve both cognitive and motor functions. Although hypoxic-ischemic encephalopathy induced significant expression of caspase-3 and Beclin-2, human umbilical cord mesenchymal stem cells decreased the expression of both of them. Human umbilical cord mesenchymal stem cells may serve as a potential treatment to ameliorate brain injury in hypoxic-ischemic encephalopathy patients.